Kadar Bahan Organik Tanah pada Tanah Sawah dan Tegalan di Bali serta Hubungannya dengan Tekstur Tanah - TANGKETASIK, AGUSTINA; WIKARNITI, NI MADE; SONIARI, NI NENGAH; NARKA, I WAYAN (Agrotrop : Journal on Agriculture Science, 2014)
Recently, the soil organic matter was exposed decrease rapidly. The intensive soil tillage and application anorganic fertilizer to suppose decrease soil organic matter. How low organic matter content of paddy soil and uppland soil not yet were taken. Soil sample of paddy soil and upland soil were taken from regency in Bali. Number of soil sample was 96 consisted of 48 soil samples from paddy soil and 48 from uppland soil. For each regency was taken 4 - 5 soil samples with random sampling. Soil sample was analyzed at Laboratorium Tanah Fakultas Pertanian Universitas Udayana. Organic matter content was analyzed with Walkley dan Black method and soil texture was analyzed with Pipet method. Organic matter content of paddy soil were correlated with soil texture (sand, silt and clay), and of uppland soil were correlated with soil texture (sand, silt and clay). Result of this experiment showed that, soil organic matter of paddy soil was higer than uppland soil. Soil organic matter of paddy soil with criteria very high 4.17 %, high 27.08 %, moderate 47.92 %, low 18.75 % and very low 2.08 %. Soil organic matter of uppland soil with criteria : high 6.25 %, moderate 35.42 %, low 39,58 % and very low 18.75 %. Fine texture was dominant of paddy soil, but coarse texture was dominant at uppland soil. Correlation between soil organic matter to soil texture of uppland soil was better than correlation between soil organic matter with soil texture at paddy soil. Correlation soil organic matter with texture (sand) at uppland soil r = -0.5142*) and correlation with clay r = 0.5007*. Correlation at paddy soil between sand and soil organic matter r = -0.1241 and between clay and organic matter of soils r = 0.2150.
Keywords: Organic matter, soil texture, paddy soil, uppland soil